Impact of Rise in Atmosphere Temperature on an Official Building’s Energy Consumption in Kathmandu - Pandit, Sameer; Bhattarai, Nawraj (Journal of the Institute of Engineering, 2018)
The objective of this research is to study the impact of rise in atmospheric temperature, in buildings energy consumption in the future. An existing Typical Meteorological Year (TMY) weather file of time span 1973-1996 composed of weather data by Solar and Wind Energy Resource Assessment (SWERA) project is assumed as the baseline climate in this study. Monthly average temperature of future years in business as usual scenario predicted by Meteonorm is downscaled to hourly temperature data using downscaling method, morphing. This showed that annual average air temperature of the atmosphere will increase by 1.64¬0C, 2.12¬0C, 2.52¬0C and 2.28¬0C from baseline year in the years 2010, 2020, 2030, and 2040 respectively. Building energy simulation tool eQUEST is used to analyze the energy consumption pattern of a selected building located in Kathmandu. Study has shown that total energy consumption of the building for heating, cooling, lighting and miscellanies equipment will increase by 4.9%, 6.2%, 7.3% and 8.3% for the years 2010, 2020, 2030 and 2040 respectively from baseline year whereas cooling load will increase by 19%, 23%, 27% and 31%. The study also has shown that insulating a building will decrease the energy consumption. There will be decrease in the cooling energy consumption by 2.29%, 2.98%, 4.06% and 4.78% in the years 2010, 2020, 2030 and 2040 respectively after addition of insulation material mineral wool/fiber. Journal of the Institute of Engineering, 2017, 13(1): 102-107